ATRT-38. TAK228 COMBINES WITH NAVITOCLAX TO ENHANCE PLATINUM-INDUCED CYTOTOXICITY IN AT/RT. Issue 2 (22nd June 2018) - Rubens, Jeffrey; Wang, Sabrina; Sharma, Shreya; Shah, Smit; Warren, Kathy; Eberhart, Charles; Raabe, Eric
Abstract: Survival in atypical teratoid rhabdoid tumors (AT/RT) is plagued by drug resistance to platinum-intensive therapies. We have previously shown the dual mTORC1/2 inhibitor TAK228 (aka MLN0128) extends survival in orthotopic mouse models of AT/RT by enhancing cisplatin-induced apoptosis. TAK228 decreases expression of the anti-apoptotic protein MCL-1 but leads to a reflexive increase in anti-apoptotic proteins BCL-2 and BCL-XL . We hypothesize that combining TAK228 with the BH3 mimetic, navitoclax will enhance platinum-induced cytotoxicity, reduce drug resistance, and extend survival in AT/RT. TAK228 combined with navitoclax decreases expression of MCL-1, BCL-2, and BCL-XL ; shifting toward a pro-apoptotic balance of BCL-2 family proteins. Navitoclax combines synergistically with TAK228 to slow AT/RT cell growth (MTS assay, p<0.01 t-test; MUSE viability assay, p<0.01 ANOVA) and enhances carboplatin-induced cytotoxicity (MUSE Annexin-V, p<0.01 by ANOVA; western for c-PARP). Clinical trials identify 30mg TAK228 weekly as the maximum tolerated dose in adults, which converts to 6mg/kg in mice. This dose penetrates AT/RT orthotopic xenograft tumors within 1 hour of oral administration, inhibits mTORC1/2 activation, and decreases MCL-1 expression until 48 hours after administration. Clinical trials of navitoclax reveal a similar rapid onset of activity with pre-clinical evidence of CNS penetration. Our pilot experiments find combinations of TAK228, navitoclax, and carboplatin are well tolerated in mice. Long term survival studies are ongoing. We are currently developing a phase I clinical trial testing TAK228 combined with carboplatin to treat relapsed pediatric brain tumors with plans for follow-up studies adding navitoclax to enhance the efficacy of this drug combination.